Status and Perspective of China’s Nuclear Safety Philosophy and Requirements in the Post-Fukushima Era - Yang, Zhiyi; Li, Fengchen; Chai, Guohan (Frontiers in Energy Research, 2022)
The significant impact brought by a severe nuclear accident at the Fukushima Daiichi Nuclear Power Plant (NPP) in Japan in March 2011 has made global regulators to review the requirements against severe accidents. In China, comprehensive safety inspection and external hazard safety margin assessment on NPPs were carried out, regulatory requirements on improvement measures for NPPs based on the inspection were given, the nuclear safety 5-year plan was made and executed, and the safety requirements on the new NPP design were drafted. The Nuclear Safety Law came into effect in 2018. The “Code on the Safety of Nuclear Power Plant Design” (HAF102) was revised in 2016, and relevant safety guides were developed. In this article, improvement actions and requirements about NPP safety in China over the past 10 years were reviewed, and the nuclear safety philosophy and requirements including practical elimination, classification of accident conditions, and defense in depth portable equipment were elaborated. In summary, some suggestions of NPP safety in China in the future were provided.